Kegiatan Sosialisasi Penyusunan Butir Soal Berbasis Hots Bagi Guru-Guru Smp/Smk Swasta Nusantara Tanah Jawa - Sijabat, Osco Parmonangan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Assessment of student learning outcomes can help improve higher order thinking skills (HOTS), because higher order thinking encourages students to think broadly and deeply about subject matter. Based on the results of the international study, the Program for International Student Assessment (PISA), Indonesian students' achievements in reading literacy, mathematical literacy and scientific literacy are very low. In general, Indonesian students' abilities are very low in: (1) understanding complex information; (2) theory, analysis and problem solving; (3) use of tools, procedures and problem solving; and (4) conducting investigations. Based on the facts above, it is necessary to change the system in learning and assessment. Assessments developed by teachers are expected to encourage increased high-level thinking abilities, increase creativity, and build students' independence to solve problems. Therefore, a team of lecturers from HKBP Nommensen Pematangsiantar University carried out community service activities through socialization on the preparation of questions based on Higher Order Thinking Skills for SMP/SMK Swasta Nusantara Tanah Jawa. The implementation of this HOTS-based question item preparation socialization activity was carried out using lecture and simulation methods. This activity is carried out by providing training and assistance in preparing HOTS-based questions in accordance with the question writing guidelines. The results obtained after this activity was carried out were that 89% of the teachers at SMP/SMK Swasta Nusantara Tanah Jawa had understood the concept and were able to prepare HOTS questions for all available subjects. Thus, it can be concluded that the socialization activity for preparing HOTS-based questions went smoothly and effectively.